Assessment of socio-economic factors affecting the utilization of manual screw press for gari production in Kwara state, Nigeria - Adegbola Adetayo Jacob; Wegh Francis Shagbaor; Ikwuba Agnes Agbanugo; Nwafor Solomon Chimela (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2019)
This study investigated socio-economic determinants of utilization of manual screw press for cassava mash dehydration for gari production in four local government areas across the ADP zones in Kwara state, Nigeria. Using random sampling technique and a semi-structured questionnaire as research instrument, data for the study were collected from a sample of three hundred and eighty four (384) gari processors who use the screw press in the state. Multiple regression analysis show that a correlation (R=0.678) exist between utilization of the screw press and the independent variables which include age, household size, level of education, years of processing experience, extension visits, and  income from gari processing. R2 value of 0.460 indicates that about 46% of the variation in utilization was explained by socio-economic variables included in the regression model. Three variables significantly influenced the decision of the respondents to utilize the manual screw press: age, level of experience, and income; the most important predicator being income with a Beta value of 0.699. Conclusively, it was recommended among others that research, extension, and policy makers consider the significant determinants identified in the study seriously if increased utilization is to be achieved by gari processors and others similar to them in the study area and the region.